The Use of Azhari Curriculum in Arabic Language Learning at Islamic Boarding School - Eka Fitria Fidayani; Farikh Marzuki Ammar (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
eLKISI Islamic Boarding School adapts the curriculum from Al-Azhar Cairo or what is called the Az-Azhar curriculum. The Al-Azhar curriculum is a foreign curriculum adapted in Indonesia through the Cakrawala Insan Azhari Foundation as an institution that bridges the eLKISI Islamic Center Islamic Boarding School in implementing this curriculum. The purpose of this study is to know and understand the preparation for learning Arabic with the Al-Azhar curriculum at the Islamic Center eLKISI Islamic Boarding School; in order to know and understand the implementation of learning Arabic with the Al-Azhar curriculum at the eLKISI Islamic Boarding School; as well as to know and understand the learning evaluation process with the Al-Azhar curriculum at the Islamic Center Islamic Boarding School eLKISI. This study uses a qualitative method. The research was conducted by means of interviews, observation and then analyzing the data. The results of the analysis will be carried out by reducing data, presenting data and drawing conclusions. From the data presented, the research entitled